Biological Monitoring: Evidence for Reductions in Occupational Exposure and Risk - Morton, Jackie; Sams, Craig; Leese, Elizabeth; Garner, Fiona; Iqbal, Shahwaiz; Jones, Kate (Frontiers in Toxicology, 2022)
Aims This publication explores occupational exposure trends from biological monitoring data collected over more than 20 years. The data were collated for all biological monitoring results for lead, mercury, benzene, and hexamethylene diisocyanate exposures where there have been some regulatory drivers within the reported time period of the data searched. Methods Relevant results from sample analysed were extracted from the database and categorised by year from 1996 to the end of 2019 for individual blood lead results and individual urine results for mercury, benzene, and hexamethylene diisocyanate. Results were classed by broad occupational sector where possible and 90th percentile (P90)) and number of samples per year were evaluated for each year and over six-year periods. Results Between 1996-2019, 37 474 blood lead, 11 723 urinary mercury, 9 188 urinary S-phenylmercapturic acid (SPMA, benzene metabolite) and 21 955 urinary hexamethylene diamine (HDA, metabolite of hexamethylene diisocyanate, HDI) samples were analysed and reported. Over the time period blood lead P90 concentrations reduced from 53 µg/dL (1996) to 24 µg/dL in 2019; P90 urinary mercury levels reduced from 13.7 µmol/mol creatinine to 2.1 µmol/mol creatinine and P90 urinary SPMA levels reduced from 133.7 µmol/mol creatinine to 1.7 µmol/mol creatinine. For HDI the P90 results reduced from 2 µmol HDA/mol creatinine in 1996-2000 to 0.7 in 2005-2010 but levels have since increased to 1.0 µmol HDA/mol creatinine. Conclusions There is strong evidence of reductions in exposure of GB workers to lead, benzene and mercury from the data presented here. These reductions may reflect the impact of national, regional and global regulatory action to reduce exposures however, the loss of high exposure industries (from either GB as a whole or just this dataset i.e. samples are being sent elsewhere) and the increase in automation or substitution also need to be considered as potential factors. The results for HDI show that whilst interventions can reduce exposures significantly, such initiatives may need to be refreshed at intervals to maintain the reductions in exposure. Waste and recycling (lead, mercury) and tunnelling through contaminated land (benzene) were sectors associated with significant exposures may be increasingly areas of concern.